A simple score to estimate the likelihood of pseudoprogression vs. recurrence following stereotactic radiosurgery for brain metastases: The Bergen Criteria. Issue 1 (10th March 2020) - Skeie, Bente Sandvei; Enger, Per Øyvind; Knisely, Jonathan; Pedersen, Paal-Henning; Heggdal, Jan Ingeman; Eide, Geir Egil; Skeie, Geir Olve
Abstract: Background: A major challenge in the follow-up of patients treated with stereotactic radiosurgery (SRS) for brain metastases (BM) is to distinguish pseudoprogression (PP) from tumor recurrence (TR). The aim of the study was to develop a clinical risk assessment score. Methods: Follow-up images of 87 of 97 consecutive patients treated with SRS for 348 BM were analyzed. Of these, 100 (28.7%) BM in 48 (53.9%) patients responded with either TR ( n = 53, 15%) or PP ( n = 47, 14%). Differences between the 2 groups were analyzed and used to develop a risk assessment score (the Bergen Criteria). Results: Factors associated with a higher incidence of PP vs. TR were as follows: prior radiation with whole brain radiotherapy or SRS ( P = .001), target cover ratio ≥98% ( P = .048), BM volume ≤2 cm 3 ( P = .054), and primary lung cancer vs. other cancer types ( P = .084). Based on the presence (0) or absence (1) of these 5 characteristics, the Bergen Criteria was established. A total score <2 points was associated with 100% PP, 2 points with 57% PP and 43% TR, 3 points with 57% TR and 43% PP, whereas >3 points were associated with 84% TR and 16% PP, P < .001. Conclusion: Based on 5 characteristics at the time of SRS the Bergen Criteria could robustly differentiate between PP vs. TR following SRS. The score is user-friendly and provides a useful tool to guide the decision making whether to retreat or observe at appropriate follow-up intervals.